Barotropic Kelvin Wave‐Induced Bottom Boundary Layer Warming Along the West Antarctic Peninsula. Issue 3 (10th March 2019) - Webb, D. J.; Holmes, R. M.; Spence, P.; England, M. H.
Abstract: Intrusions of warm circumpolar deep water onto the Antarctic continental shelf are thought to drive accelerated loss of Antarctic glacial ice mass by triggering melt at the ice shelf grounding line. However, the mechanisms responsible for driving on‐shelf circumpolar deep water intrusions are not well understood. Here we examine how sea surface height (SSH) anomalies propagating around the Antarctic coastline as coastal‐trapped waves can drive warm water intrusions through changes in bottom Ekman transport. A wind perturbation motivated by the recent intensification and poleward shift of the southern annular mode during its positive phase is applied over Eastern Antarctica between 20°E and 120°E in two global ocean sea‐ice models (1/4° and 1/10°) and a single‐layer shallow water model. The changes in winds generate a drop in coastal SSH that propagates around Antarctica as a barotropic Kelvin wave. The SSH drop is accompanied by a barotropic flow, which alters the bottom stress, generating an onshore transport of warm water wherever thermal gradients are favorable. We estimate the resulting anomalous bottom Ekman flow and use temperature gradients calculated from the Southern Ocean State Estimate, along with the 1/4° and 1/10° models, to evaluate the resultant heat advection. We find that this mechanism can drive warming of up to 0.7 °C along the West Antarctic Peninsula within a year, depending on the mean state of the cross‐shelf temperature gradient and the barotropic flow strength. Over longer time scales, warming eventually ceases due to saturation of the SSH field and arrest of the Ekman transport by buoyancy forces. Plain Language Summary: Antarctic glacial ice melt has accelerated in recent years, yet we still do not fully understand the mechanisms driving this increased melt. Part of the answer is thought to lie in intrusions of warm subsurface waters that come into contact with the base of Antarctica's ice shelves. However, the processes that drive these warm water intrusions are not yet well understood. Here we examine a mechanism for wind‐driven changes in coastal sea level that propagate around Antarctica as coastal‐trapped waves and consequently drive onshore heat transport via changes in bottom layer flow. We calculate an estimate for the warming rate associated with this mechanism using theory; model simulations; and, where available, observations. We further test the sensitivity of heat transport to local stratification as well as a parameter that determines the bottom flow strength. Each model simulation is forced with winds based on projections of an intensified westerly wind belt over the East Antarctic sector of the Southern Ocean. In each case we find substantial subsurface warming to develop along the West Antarctic Peninsula within 1 year, with the strongest warming seen where the net coastal flow, and the temperature gradients over the Antarctic continental shelf are greatest. Key Points: We examine the response of the Antarctic margin to East Antarctic wind anomalies based on an intensified southern annular mode Barotropic Kelvin waves propagate the signal around Antarctica, leading to changes in bottom stress, bottom Ekman transport, and near‐bottom temperature We quantify model‐simulated warming rates along the West Antarctic Peninsula that can be attributed to Kelvin wave‐induced bottom Ekman flow under an idealized wind forcing scenario